点啮合球锥滚子弧面分度凸轮机构的接触应力分析 - 赵雪妮; 曹巨; 江卢军 (Jixie chuandong)
In this paper, based on the analysis of the globoidal indexing cam, the sphere-conical roller globoidal indexing cam mechanism was presented. contact stress of the mechanism was calculated and the contact strength was analyzed. This provided the theory basis for future studying on the mechanism.